Monetary policy and exchange rates in different economic contexts: Case study of South Africa - Choga, Simba (Department of Finance and Tax, 2023)
The aim of this study is to examine the relationship between the interest rate and money supply with the exchange rate in South Africa in three periods:- before the global financial crisis (GFC) (Jan 2002 – Jan 2007), during the GFC (Jan 2008 – Dec 2009) and after the GFC (Jan 2010 – Jan 2016). No clear direction on the relationship between the monetary policy and the exchange rate has been ascertained in developing and developed economies. The Autoregressive-Distributed Lag (ARDL) model is utilized to find the objective of this study. Not much research has taken place involving the relationship of the interest rates, money supply with the exchange rate in the context of South Africa. To my knowledge this is the first study that incorporates the ARDL model to try and ascertain the type of relationship these variables have in South Africa. Therefore, new insights are yielded in the academic arena from this research's results. The results show that there is no significant relationship between the money supply and the exchange rate both in the short and long run in all three economic contexts. A significant effect is found from the interest rate on the exchange rate in the short run during and after the GFC. However, no relationship is found before the GFC between the interest rate and exchange rate. In addition, no relationship is found in the long run between the variables in all three economic contexts. The results suggest that the South African Reserve Bank SARB had a huge influence on the exchange rate during and after the GFC through changing the repo rate.